Increased rates of blood culture contamination during the coronavirus disease 2019 pandemic. (24th November 2022) - Esquer Garrigos, Zerelda; Wingler, Mary Joyce B.; Svoronos, Petros A.; Vijayvargiya, Prakhar; Goodman-Meza, David; O'Horo, John C.; Navalkele, Bhagyashri D.; Cretella, David; Frame, Ithiel J.; Parham, Jason; Lucar, Jose
Abstract: We observed a higher rate of blood-culture contamination during the COVID-19 pandemic at our institution compared to a prepandemic period. Given the potential implications of blood contamination in antibiotic and diagnostic test utilization as well as added cost, it is imperative to continue efforts to minimize these episodes during the pandemic.